Generalised semi-empirical correlation for heat transfer in channels of plate heat exchanger - Arsenyeva, O. P.; Tovazhnyanskyy, Leonid Leonidovich; Kapustenko, P. O.; Demirskiy, O. V. (Elsevier Inc., 2014)
The analogy of heat and momentum transfer in turbulent flow modified for channels of Plate Heat Exchanger (PHE) is proposed. The effects of channel geometry, flow velocity and fluid properties on heat transfer are accounted in the resulting equation, which permits the calculation of film heat transfer coefficients using the generalized correlation for friction factor at the main corrugated field of the interplate channel. The results of calculations are compared with data from experimental study. The good accuracy of film heat transfer coefficients prediction is shown. In the case when the corrugations direction is parallel to the flow direction, the calculations results are quite close to the predicted by the Equation published in the literature for straight pipes. The Prandtl number influence on heat transfer is discussed and semi-empirical Equation for its evaluation is proposed. The comparison with experimental data available in the literature confirmed the accuracy of the heat transfer prediction. The proposed Equation is recommended to be used for optimization of PHEs channels geometry for different conditions in the process industries. It can be employed also for optimizing PHEs heat exchange networks and also to determine PHEs heat transfer area targets when process integration methodology is employed.
Keywords: plate heat exchanger; heat transfer; momentum transfer; friction factor; Prandtl number; Reynolds number